Forage corn yield and nutritive quality under different plant densities and tillage systems - Baghdadi, Ali (2012)
Plant density and tillage methods are two important factors affecting forage corn production. A field experiment was conducted in the summer of 2010 in northern Iran to evaluate the response of yield and yield components and nutritive quality of forage corn to various plant densities under different tillage methods. The experiment used a split-plot design with tillage as the main plot in three replications and plant density as the subplots within each tillage method. The plant densities were 90,000, 110,000 and 130,000 plants per hectare and the tillage methods were conventional tillage (CT), reduced tillage (RT), minimum tillage (MT) and no-tillage (NT). The results of the study showed that plant density affected yield components, including forage dry matter (DM) yield, fresh forage yield, stem diameter, leaf area index (LAI), crop growth rate (CGR), leaf to stem ratio and cob/whole plant ratio. At the high plant density (130,000 plants ha-1), the forage yield (57.3 t ha-1) was higher than the normal plant density used in the northern part of the country (110,000 plants ha-1) by 16.75%. In terms of dry matter the highest yield was achieved for the highest plant density (16.5 t ha-1) and the minimum was obtained for the lowest plant density (14.3 t ha-1). Low plant density resulted in high stem diameter (1.93 cm). Lowest leaf to stem ratio (0.40) and cob/whole plant ratio (0.41) were obtained at high plant density as compared to low and usual plant density. Maximum LAI (4.59) and CGR (39.63 g m-2 day-1) were recorded at the highest plant density Increasing plant density reduced the nutritive quality of forage corn. The crude protein (CP) declined from 125 to 99 g kg-1 from the lowest to the highest plant density. Acid detergent fiber (ADF) increased from 156.9 to 197.5 g kg-1 from the lowest to the highest plant density. Dry matter digestibility (DMD) decreased from 689.9 to 655.0 g kg-1 from lowest to highest plant density. Tillage methods had significant effects on dry matter (DM) yield, fresh forage yield, stem height and number of leaves of forage corn while the nutritive value of corn was not significantly affected. Conventional tillage resulted in dry matter yield of 17.1 t ha-1 which was not significantly different from the dry matter yield for reduced tillage (16.2 t ha-1). However minimum tillage (14.6 tha-1) and no tillage (13.7 t ha-1) showed significantly lower dry matter yield than conventional tillage. Maximum CGR (35.5 g m-2 day-1) and LAI (4.30) were recorded for conventional tillage method. It is recommended that reduced tillage (two passes of rotary tiller) should be practised for planting corn in north of Iran as it benefits soil conservation without any reduction in yield compared to conventional tillage (mouldboard plow followed by two passes of rotary tiller). Plant density of 130,000 plants ha-1 result in the best potential for increased forage corn yield compared to lower plant densities. The slight reduction in nutritive quality at high plant density is compensated by the higher yield obtained.